Comparison between Standardized Precipitation Index (SPI) and Standardized Precipitation Evapotranspiration Index (SPEI) Methods to Identify Meteorological Drought in West Papua - Arif Faisol; Budiyono Budiyono (Fakultas Teknologi Pertanian, Universitas Papua, Manokwari, 2022)
The Standardized Precipitation Index (SPI) and Standardized Precipitation Evapotranspiration Index (SPEI) methods have been widely used to monitor meteorological droughts, especially in Indonesia. This study aims to compare the SPI and SPEI methods in identifying meteorological drought in West Papua. This research consists of 3 (three) main stages, i.e., climate data inventory acquired from 1996 to 2020, drought level analysis using SPI and SPEI methods, and comparison SPI and SPEI drought index. The results showed that the drought level in West Papua is moderately dry to moderately wet based on the SPI method, and near normal to moderately wet based on the SPEI method. Generally, the SPI and SPEI methods have a strong correlation in analyzing drought in West Papua although in some periods there were significant differences in index values.